Lactotransferrin-Related Breast Amyloidosis: Report of a First Case. (February 2022) - Yan, Mingfei; Rodgers, Mark; Harbhajanka, Aparna; Gilmore, Hannah
Breast amyloidosis is a rare condition which is mostly associated with hematological disorders or hereditary genetic disorders. Imaging findings of breast amyloidosis can mimic malignancy, which often leads to biopsy or excision of the lesion. Here, we presented a case of localized lactotransferrin-related breast amyloidosis in an elderly female patient. Histologic examination revealed extensive involvement of breast lobules by amorphous amyloid materials, with attenuation of lobular structures and prominent calcifications. Positive immunostains for myoepithelial cells helped to exclude the possibility of invasive carcinoma. The patient had no hematologic malignancy besides immunoglobulin G lambda monoclonal gammopathy of undetermined significance. Mass spectrometry of the breast amyloid identified lactotransferrin and no immunoglobulin or its light chain. On follow-up, the patient showed no recurrence of the breast lesion after local excision nor showed other systematic comorbidities, indicating the benign nature of the lesion. This first report of lactotransferrin-related amyloidosis may represent a special type of localized breast amyloidosis that has no correlation with systematic disorders.